Effects of dietary supplementation of quillaja saponin or fructooligosaccharide and a mixture of both on the growth performance, nutrient utilisation, faecal microbial and faecal noxious gas emissions in growing pigs - Madesh Muniyappan; Dong Heon Baek; In Ho Kim (Italian Journal of Animal Science, 2022)
The objective of this experiment was to evaluate the effect of an alone or in combination quillaja saponin (QS) and fructooligosaccharide (FOS) on the growth performance, nutrient utilisation, faecal microbial and faecal noxious gas emissions in growing pigs. A total of 100 pigs (Landrace × Yorkshire × Duroc); weighted 23.83 ± 1.95 kg, were selected and randomly allocated to 4 treatments with 5 replicates per group and 5 pigs per replicate according to the initial body weight and sex. The experimental treatments were as follows: (1) basal diet (Ctrl); (2) Ctrl + 0.2% QS; (3) Ctrl + 0.10% FOS; (4) Ctrl + 0.2% QS + 0.10% FOS (QSFOS). The experiment period lasted for 56 days. Pigs fed a diet supplemented with QS, FOS and QSFOS resulted in an increase (p < 0.05) in body weight (BW) on days 28 and 56, (p < 0.05) average daily gain and average daily feed intake during days 28–56 and 50–56, as well as improved apparent total tract digestibility (ATTD) of DM (dry matter) and N (Nitrogen) during day 56 compared with Ctrl. The faecal Lactobacillus counts were increased and a reduction (p < 0.05) in faecal Escherichia coli (E. coli) counts and ammonia (NH3) and carbon dioxide (CO2) emission from the faeces was observed from pigs fed QS, FOS and QSFOS supplemented diets compared with those fed a Ctrl diet. In conclusion, dietary QS, FOS and QSFOS supplementation have beneficial effects on growth performance, nutrient utilisation, faecal microbial and noxious gas emissions in growing pigs.HIGHLIGHTS Dietary supplementation of QS, FOS and QSFOS increased body weight, average daily gain and average daily feed intake of growing pigs. Dietary supplementation of QS, FOS and QSFOS could improve ATTD of dry matter and nitrogen of growing pigs Dietary supplementation of QS, FOS and QSFOS increased Lactobacillus counts and reduced E. coli counts of growing pigs. Dietary supplementation of QS, FOS and QSFOS could reduce faecal NH3 and CO2 emissions of growing pigs.